CTRP3 protects hippocampal neurons from oxygen-glucose deprivation-induced injury through the AMPK/Nrf2/ARE pathway. (July 2021) - Ding, H; Wang, Z; Song, W
Objective: C1q/TNF-related protein 3 (CTRP3), a member of CTRP family, has been found to have neuroprotective effect. In the current study, we investigated the protective role of CTRP3 in hippocampal neurons exposed to oxygen-glucose deprivation/reperfusion (OGD/R). Materials and methods: The mRNA and protein levels of CTRP3 in OGD/R-stimulated hippocampal neurons were measured using qRT-PCR and western blot analysis, respectively. CCK-8 assay was performed to assess cell viability. ROS production was measured using the fluorescence probe 2′, 7′-dichlorofluorescein diacetate (H2 DCFDA). The activities of SOD and GPx were determined using ELISA. Cell apoptosis was assessed. Luciferase reporter assay was carried out to assess the activation of ARE). The levels of p-AMPK and Nrf2 were measured using western blot. Results: Our results showed that the expression of CTRP3 was significantly downregulated in hippocampal neuronal cells exposed to OGD/R. Overexpression of CTRP3 improved cell viability of OGD/R-induced hippocampal neurons. In addition, overexpression of CTRP3 attenuated the OGD/R-caused oxidative stress with decreased ROS production and increased activities of SOD and GPx. Moreover, CTRP3 caused a significant increase in bcl-2 expression and decreases in bax expression and caspase-3 activity. Furthermore, CTRP3 overexpression significantly upregulated the levels of p-AMPK and Nrf2, as well induced the activation of ARE in OGD-R-induced hippocampal neurons. CTRP3 upregulated the mRNA expression levels of HO-1, NQO-1 and GPx-3. Additionally, treatment with the inhibitor of AMPK partially reversed the neuroprotective effect of CTRP3 in OGD/R-exposed neurons. Conclusion: CTRP3 exerted protective effect on OGD/R-induced cerebral injury, which was regulated by AMPK/Nrf2/ARE pathway.